KEPATOGENAN SATELIT RNA YANG BERASOSIASI DENGAN CUCUMBER MOSAIC VIRUS (CMV-satRNA) PADA TANAMAN CABAI - Hasriadi Mat Akin . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2005)
Pathogenicity of RNA satellite associated with cucumber mosaic virus (CMV-satRNA) on hot pepper plant. The objective of this experiment was to determine the pathogenicity of RNA satellite associated with CMV (CMV-satRNA) on hot pepper plant and effects of mix infection of CMV-satRNA and other viruses naturally infecting hot pepper, PVY (potato virus Y) and TMV (tobacco mosaic virus). Two green house experiments were conducted in Gedong Meneng Bandar Lampung during June—November 2004. The treatments of the the first experiment were arranged in a completely randomized design with five replications. The treatments were hot pepper plant inoculated with CMV-satRNA, severe strain CMV-G, and control uninoculated plant. The second treatment was arranged in a complete block randomized design in a factorial experiment with four replications. The first factor was single inoculation of CMV-satRNA, PVY, TMV, double inoculatoin of CMV-satRNA and PVY, CMV-satRNA and TMV, PVY and TMV, and control uninoculated plant. The second factor was two hot varieties, Taro and Laris. The results of the first experiment showed that infection of CMV-satRNA did not significantly reduce the yield of hot pepper plant compared to severe strain CMV-G. The result of the second experiment indicated that mix infection of CMV-satRNA and TMV or CMV-satRNA and PVY did not induced a synergetic reaction on hot pepper plants.